2021
DOI: 10.1017/s1092852921000547
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness among 500 people living homeless and referred for psychiatric evaluation in Lisbon, Portugal

Abstract: Background Our goal was to identify the demographic profile of the people living homeless with mental illness in Lisboa, Portugal, and their relationship with the national healthcare system. We also tried to understand which factors contribute to the number and duration of psychiatric admissions among these homeless people. Methods We used a cross-sectional design, collecting data for 4 years among homeless people, in Lisboa, Portugal, that were referred as possible psychiatric patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Fazel’s ( 8 ) systematic review and meta-regression analysis, drawing on data from 5684 homeless individuals, reported the prevalence of PD among the homeless in Western countries as 23.1% (CI 15.5%–30.8%). Similar data were observed in a population of 500 homeless patients in Portugal ( 13 ) and in Germany ( 14 ) both at 24%. While in Stockholm, a prevalence of 12% was reported in 1704 homeless patients receiving hospital care ( 15 ).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Fazel’s ( 8 ) systematic review and meta-regression analysis, drawing on data from 5684 homeless individuals, reported the prevalence of PD among the homeless in Western countries as 23.1% (CI 15.5%–30.8%). Similar data were observed in a population of 500 homeless patients in Portugal ( 13 ) and in Germany ( 14 ) both at 24%. While in Stockholm, a prevalence of 12% was reported in 1704 homeless patients receiving hospital care ( 15 ).…”
Section: Resultssupporting
confidence: 84%
“…A substantial number of psychiatric disorders are well documented in homeless populations ( 13 ). Homeless people with multiple diagnoses have greater mental health needs and worse general health determinants ( 9 , 13 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At that time, authors suggested that further studies were needed for a better understanding of schizoaffective disorder among the homeless population (Nardacci et al, 1993). In more recent European studies, of 500 homeless people, the prevalence of schizoaffective disorder was 11% (Monteiro Fernandes et al, 2021), and the homeless with schizoaffective disorder had a statistically significant longer follow-ups, a higher median of psychiatric hospitalizations, and a higher median duration of total psychiatric hospitalizations (Ayano et al, 2019). Therefore, following the scarce existence of literature regarding the topic (Fazel et al, 2008), the authors propose to do a review aiming to study the relation between schizoaffective disorder and homelessness.…”
Section: The Schizoaffective Disorder In the Homelessmentioning
confidence: 99%
“…Bento and Barreto (2002) have been working with homeless people with mental illness, with different organizations, for a large number of years that altogether surpass the fifty years mark. To this day, they provide scientific literature regarding mental illness of homeless people, contributing to Portuguese studies (Monteiro Fernandes et al, 2022) and European guidelines (Barreto et al, 2019). Bento and Barreto (2002) could easily be considered our charismatic leaders who could bring people together and who held on to a vision, two of a kind of that homelessness needed champion especially in nonhousing agencies such as the health authority (Pannel & Parry, 1999).…”
Section: Discussionmentioning
confidence: 99%